1985
DOI: 10.1021/ic00213a041
|View full text |Cite
|
Sign up to set email alerts
|

Structures of bis(1-thia-4,7-diazacyclononane)copper(II) nitrate and bis(1,7-diaza-4-thiaheptane)copper(II) nitrate. A different conformation for the coordinated macrocycle

Abstract: Die beiden Titelkomplexe (I) und (II) werden durch Umsetzung von Cu(II)‐nitrattrihydrat mit den entsprechenden Liganden in Ethanol bzw. Methanol synthetisiert und durch Röntgenstrukturanalysen [(1): RG Pbca, Z=4; (II): RG PI, Z=2] sowie Elektronenspektren charakterisiert.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
10
0

Year Published

1985
1985
2019
2019

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(11 citation statements)
references
References 0 publications
1
10
0
Order By: Relevance
“…In all complexes of the related ligand tacn (l,4,7-triazacyclononane), the conformation with all rings having the same chirality (222 or ~6b') is present, and this arrangement has also been found in I Ni(tasn)21(NO3) 2 (Hart, Boeyens, Michael & Hancock, 1983). The conformation found here has been observed previously in the structure of ICu(tasn)21(NO3) 2 (Boeyens, Dobson & Hancock, 1985). In that report it was suggested that the mixed-chirality conformation was stabilized by the longer metal-to-donor-atom bond lengths of the copper complex compared to the nickel complex.…”
Section: Discussion Structure (I) (Trans)supporting
confidence: 84%
See 1 more Smart Citation
“…In all complexes of the related ligand tacn (l,4,7-triazacyclononane), the conformation with all rings having the same chirality (222 or ~6b') is present, and this arrangement has also been found in I Ni(tasn)21(NO3) 2 (Hart, Boeyens, Michael & Hancock, 1983). The conformation found here has been observed previously in the structure of ICu(tasn)21(NO3) 2 (Boeyens, Dobson & Hancock, 1985). In that report it was suggested that the mixed-chirality conformation was stabilized by the longer metal-to-donor-atom bond lengths of the copper complex compared to the nickel complex.…”
Section: Discussion Structure (I) (Trans)supporting
confidence: 84%
“…Two geometric isomers are possible for octahedral IM(tasn)21 -'~ complexes, designated cis and trans according to the arrangement of the S atoms about the metal. Structures of both [Cu(tasn)El(NO3) 2 and [Ni(tasn)El(NO3) 2 have revealed the trans isomer (Boeyens, Dobson & Hancock, 1985;Hart, Boeyens, Michael & Hancock, 1983). Preparation of the Co I~ complex was first described by Gahan, Lawrance & Sargeson (1982) and they and Nonoyama & Ishida (1984) obtained spectroscopic evidence for the existence of more than one isomer.…”
Section: Trans-bis(1-thia-47-diazacyclononane)-cobalt(iii) Trifluoromentioning
confidence: 99%
“…The formation of the dihydrobromide salt of 1,4-diaza-7-thiacyclononane (11) was achieved by literature procedures (10,11) and proceeds with reasonable yields. Care must be taken during the detosylation of the amines to avoid cleavage of the C-S bonds with the ring.…”
Section: Synthesis and Spectroscopymentioning
confidence: 99%
“…Besides biochemical relevance, sulfur-containing chelates with firs-row transition metals are also of more general coordination chemistry interest _ The soft character of the sulfur ligand allows investigations concerning the influence upon electronic spectroscopy [ll, 15-171, the stabilization of low valent oxidation states , the stereochemical properties [15][16][17]211 and even the potential application in homogeneous catalysis [ 191. With this purpose the ligands 1,12-bis(3,5di-methylpyrazol-1 -yl)-2,ll diaza_5,8dithiadodecane, abbreviated dsbd, and l,l,lO,lO-tetrakis(3,5di-methylpyrazol-l-ylmethyl)-l,1Odiaza-4,7dithiadecane, abbreviated dstd, were synthesized and their coordination chemistry towards first-row transition metals was investigated. The dsbd ligand combines two thioether sulfur atoms, two secondary amines and two pyrazole rings in a conformation which would allow chelation to one metal ion, thus yielding a potentially hexadentate ligand.…”
Section: -1693/88/$350mentioning
confidence: 99%